Longitudinal analysis of human humoral responses after vaccination with a live attenuated V. cholerae vaccine. - Oluwaseyi Adekunle (Public Library of Science (PLoS), 2021)
Vibrio cholerae is a bacterial pathogen which causes the severe acute diarrheal disease cholera. Given that a symptomatic incident of cholera can lead to long term protection, a thorough understanding of the immune response to this pathogen is needed to identify parameters critical to the generation and durability of immunity. To approach this, we utilized a live attenuated cholera vaccine to model the response to V. cholerae infection in 12 naïve subjects. We found that this live attenuated vaccine induced durable vibriocidal antibody titers that were maintained at least one year after vaccination. Similar to what we previously reported in infected patients from Bangladesh, we found that vaccination induced plasmablast responses were primarily specific to the two immunodominant antigens lipopolysaccharide (LPS) and cholera toxin (CT). Interestingly, the magnitude of the early plasmablast response at day 7 predicted the serological outcome of vaccination at day 30. However, this correlation was no longer present at later timepoints. The acute responses displayed preferential immunoglobulin isotype usage, with LPS specific cells being largely IgM or IgA producing, while cholera toxin responses were predominantly IgG. Finally, CCR9 was highly expressed on vaccine induced plasmablasts, especially on IgM and IgA producing cells, suggesting a role in migration to the gastrointestinal tract. Collectively, these findings demonstrate that the use of a live attenuated cholera vaccine is an effective tool to examine the primary and long-term immune response following V. cholerae exposure. Additionally, it provides insight into the phenotype and specificity of the cells which likely return to and mediate immunity at the intestinal mucosa. A thorough understanding of these properties both in peripheral blood and in the intestinal mucosae will inform future vaccine development against both cholera and other mucosal pathogens. Trial Registration: NCT03251495.